A Translational Framework of Educational Neuroscience in Learning Disorders - Dresler, Thomas; Bugden, Stephanie; Gouet, Camilo; Lallier, Marie; Oliveira, Darlene G.; Pinheiro-Chagas, Pedro; Pires, Ana C.; Wang, Yunqi; Zugarramurdi, Camila; Weissheimer, Janaina (Frontiers in Integrative Neuroscience, 2018)
Neuroimaging has undergone enormous progress during the last two and a half decades. The combination of neuroscientific methods and educational practice has become a focus of interdisciplinary research in order to answer more applied questions. In this realm, conditions that hamper learning success and have deleterious effects in the population – such as learning disorders (LD) – could especially profit from neuroimaging findings. At the moment, however, there is an ongoing debate about how far neuroscientific research can go to inform the practical work in educational settings. Here, we put forward a theoretical translational framework as a method of conducting neuroimaging and bridging it to education, with a main focus on dyscalculia and dyslexia. Our work seeks to represent a theoretical but mainly empirical guide on the benefits of neuroimaging, which can help people working with different aspects of LD, who need to act collaboratively to reach the full potential of neuroimaging. We provide possible ideas regarding how neuroimaging can inform LD at different levels within our multidirectional framework, i.e. mechanisms, diagnosis/prognosis, intervention/training and community/education. In addition, we discuss methodological, conceptual, and structural limitations that need to be addressed by future research.